Effectiveness of a worksite lifestyle intervention on vitality, work engagement, productivity, and sick leave: results of a randomized controlled trial - Strijk, Jorien E.; Proper, Karin I.; van Mechelen, Willem; van der Beek, Allard J. (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'A worksite lifestyle intervention aiming to improve lifestyle behaviors could be an effective tool to keep older workers vital, and thereby prolong their labor participation. Therefore, this study evaluates the effectiveness of such an intervention on vitality, work engagement, productivity and sick leave. ' ' METHODS ': 'In a randomized controlled trial design, 367 workers (control group: N=363) received a 6-month intervention, which included two weekly guided group sessions: one yoga and one workout, as well as one weekly session of aerobic exercising, without face-to-face instruction, and three individual coach visits aimed at changing workers’ lifestyle behavior by goal setting, feedback, and problem-solving strategies. Furthermore, free fruit was provided at the guided sessions. Data on work-related vitality (UWES vitality scale), general vitality (RAND-36 vitality scale), work engagement (UWES), productivity (single item scoring 0–10), and sick leave (yes/no past 3 months) were collected using questionnaires at baseline (N=730), and at 6- (N=575) and 12-months (N=500) follow-up. Effects were analyzed according to the intention-to-treat principle with complete cases (N=500) and imputed data (N=730). ' ' RESULTS ': 'There were no significant differences in vitality, work engagement, productivity, and sick leave between the intervention and control group workers after either 6- and 12-months follow-up. Yoga and workout subgroup analyses showed a 12-month favorable effect on work-related vitality [β=0.14, 95% confidence interval (95% CI) 0.04–0.28] and general vitality (β=2.9, 95% CI 0.02–5.9) among high yoga compliers. For high workout compliers, this positive trend was also seen, but it was not statistically significant. ' ' CONCLUSIONS ': 'Implementation of worksite yoga facilities could be a useful strategy to promote vitality-related work outcomes, but only if high compliance can be maximized. Therefore, impeding factors for participation should be investigated in more detail in future research.
Keywords: hospital worker; intervention; lifestyle intervention; older worker; productivity; randomized controlled trial; sick leave; sickness absence; vitality; work engagement; worksite health promotion; worksite intervention; worksite vitality intervention; yoga